2014
DOI: 10.1126/science.1249766
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Profiles of Myelin Distribution Along Single Axons of Pyramidal Neurons in the Neocortex

Abstract: Myelin is a defining feature of the vertebrate nervous system. Variability in the thickness of the myelin envelope is a structural feature affecting the conduction of neuronal signals. Conversely, the distribution of myelinated tracts along the length of axons has been assumed to be uniform. Here, we traced high-throughput electron microscopy (EM) reconstructions of single axons of pyramidal neurons in the mouse neocortex and built high-resolution maps of myelination. We find that individual neurons have disti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
513
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 498 publications
(541 citation statements)
references
References 38 publications
25
513
1
2
Order By: Relevance
“…E14.5 corresponds to a stage when key brain developmental events are taking place; neurogenesis already has reached its peak in both the nascent diencephalon and the telencephalon (2,18,19). Conversely, by 7-8 weeks of age, all major postnatal developmental milestones have been achieved, including myelination, and the mouse brain can be considered mature (20,21).…”
Section: Resultsmentioning
confidence: 99%
“…E14.5 corresponds to a stage when key brain developmental events are taking place; neurogenesis already has reached its peak in both the nascent diencephalon and the telencephalon (2,18,19). Conversely, by 7-8 weeks of age, all major postnatal developmental milestones have been achieved, including myelination, and the mouse brain can be considered mature (20,21).…”
Section: Resultsmentioning
confidence: 99%
“…This prediction would be compatible with the idea, dating back to Flechsig (2), that association cortical areas are the focus of a relatively late wave of myelinogenesis. The intracortical location of strongest maturational changes in MT, corresponding approximately to the boundary between layers V (internal pyramid) and VI, further suggests that adolescent intracortical myelination may be concentrated on the proximal segments of efferent projections from pyramidal neurons (20).…”
Section: Discussionmentioning
confidence: 99%
“…level, this signal likely reflects a developmentally late myelination of efferent axonal segments immediately distal to the axonal hillock of pyramidal cells (20). MRI sequences have been recently developed for myelin mapping in humans (21).…”
Section: Significancementioning
confidence: 99%
“…Such vision would also explain why increasing the number of the wraps 98 results in an increase in CAP speed: the thicker the sheath the more ATP is produced. A study of 99 myelin distribution along single axons showed that neocortical pyramidal in the murine brain 100 neurons comprise unmyelinated tracts, longer than previously thought (Tomassy et al, 2014).…”
mentioning
confidence: 90%
“…The classical theory assuming that the voltage gated channels are "set aside" when 109 the nerve is being wrapped from the sheath, gathering into the Ranvier Nodes, is put into serious 110 doubt in light of recent findings (Tomassy et al, 2014 Figure -Simplified picture: in an unmyelinated axonal trait the speed of the Compound Axon Potential (CAP) is low because the supply of ATP is relatively slow. In a myelinated axonal trait the speed of CAP progressively increase thanks to the ATP supply by myelin, so that the correct polarization is quickly restored.…”
mentioning
confidence: 99%